The ACDAL Framework for Parents’ Customer Journey in School Choice through Social Media Content - Mundzir, Ahmad; Iyus Wiadi (Commercium : Journal of Business and Management, 2026)
The growing role of digital platforms in educational marketing has transformed how parents engage with schools before making enrollment decisions. Previous studies have examined social media as a tool for branding and communication, yet few have explored its function as structured touchpoints within the customer journey of parents. This study introduces the ACDAL framework (Awareness, Consideration, Decision, Action, and Loyalty) to map parental engagement across different stages of school choice. Using a qualitative case study approach, data were collected from seven parents and documentation of Facebook and Instagram content published by a private junior high school in Tasikmalaya, Indonesia. Data were analyzed through content analysis to identify patterns of interaction between parents and school-generated content. The findings suggest that awareness is primarily stimulated by academic achievements and visually appealing content; consideration emerges through testimonials and program highlights; decision-making is influenced by responsive communication and transparent information; action is reflected in online and offline enrollment; and loyalty is strengthened by continuous publication of student activities and achievements. These results indicate that social media content functions as critical digital touchpoints along the parental customer journey. The study contributes to the literature by extending the customer journey model to educational settings using ACDAL and offers practical insights for schools seeking to design effective social media strategies to attract and retain parental trust.